Appropriate failure to create effective learning: Optimizing challenge - Yan, V. X.; Guadagnoli, M. A.; Haycocks, N. (Skill acquisition in sport: research, theory and practice, 2020)
When practice tails to result in positive performance during competition, it can be frustrating, but it is not without explanation. Poor competition performance often results from inappropriate preparation. More specifically, preparation that has been unintendedly designed for immediate success rather than long-term learning. At its core, poor transfer results from the learner being inappropriately challenged during practice. What follows is a brief overview of the theoretical foundations that create optimized practice and allows it to be scaled across individuals. Our approach draws from the cognitive psychology research on learning -in particular, Desirable Difficulties (Bjork, 1994) and the Challenge Point Framework (Guadagnoli & Lee, 2004). These constructs are based on research that demonstrates the benefits of appropriate failure during training and provides tools and strategies for how to use this failure to optimize learning. Complementing the cognitive approach, we also draw on socio-psychological research on motivation, namely flow and motivational beliefs. This work focuses on the benefits of shifting the concept of what failure means, promoting instead the idea that an opportunity to fail is an opportunity to learn.